Presidensialisme di Indonesia Antara Amanah Konstitusi dan Kuasa Partai - Susanto Polamolo (Jurnal Konstitusi, 2016)
Presidential power in Indonesia, was born exactly in between the mandate of the constitution, and the power of the party. Various constitutional experiments since the era of Sukarno, Suharto, to the current era of reform, shows how the starting- pull of interests, especially the interests of political parties melingkati Indonesian presidential system. The president’s powers in many respects, depend on how the political constellation, so the coalition model was prone to deadlocks, as a result of the apparent coalition. Therefore, in the future, the constitution must be addressed, and should clearly indicate the limits of political parties, so that the presidential system can really concentrate to the   people.